A urgência subjetiva na urgência e emergência médicas: a inserção da escuta psicanalítica no pronto-socorro - Costa, Clara Kislanov da (2017)
The presence of the psychoanalyst in the hospital’s emergency room still raises questions about what this professional is capable of doing in such place. The main goal of this research is to understand what is the role of the psychoanalyst in the emergency service, given the hurdles he/she can find due to a different look and a specific sense of ethics in this environment. To achieve this goal, a qualitative research was carried out, based on a theoretical discussion and a psychoanalytical reading which, in its turn, originated from the researcher experience and also from interviews with professionals from the field of Psychology. Authors like Freud, Winnicott and Roussillon were mentioned in order to give a better understanding to the main topics researched, such as the emergence of anguish, the avoidance of the traumatic and the possibilities of symbolization. In addition, this research also intends to show the importance of a care and listening that are not necessarily exclusive to the psychoanalyst. This knowledge may be used by other professionals who work in emergency units in benefit of the patient and his/her relatives